Sustainable Remediation of Atrazine in Agricultural Fields by Reusing Contaminated Water for Irrigation - Zohre Kurt (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
High yields of agricultural produce is reached traditionally by the application of fertilizers and/or pesticides. When agricultural soil is saturated with pesticides, any pesticide addition to the soil leaches and thus reaches the underlying groundwater. Preventing further contamination and remediation of this type of contamination remains to be a challenge. Although monitored natural attenuation has been shown as an ultimate solution for decontamination, additional applications have been introduced to rapidly achieve this goal. One solution that also contains economic benefits to the farmers is to pump and reuse. The study described here evaluates the possibility to use pump and reuse technique for two common pesticides with different chemical properties, namely atrazine and cypermethrin. In this study, six field samples have been evaluated for their pesticide biodegradation capacity. By placing them in sterilized controls and inoculated active columns, field conditions are replicated to study the leaching and biodegradation at the topsoil of agricultural fields. The biodegradation capacities of inoculated active columns ranged between 34 and75 mg/kg/day for atrazine. The results indicated that using the contaminated water for irrigation could eliminate the pesticide contamination from the soil and groundwater. Overall, this method provides a sustainable solution for pesticide use and remediation by minimizing the pesticide use in agricultural fields without affecting the yield of the planted crops.